TOMLINSON'S THEORY IN ARABIC LANGUAGE LEARNING INNOVATION IN INCLUSIVE SCHOOLS: TEORI TOMLINSON DALAM INOVASI PEMBELAJARAN BAHASA ARAB DI SEKOLAH INKLUSIF - Laili Mas Ulliyah Hasan; Siti Durotun Naseha; Gautama Veri Vetiana (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
Arabic language learning in inclusive schools faces challenges in accommodating the diversity of students with special needs. MTs Wachid Hasyim Surabaya, as an inclusive school, has implemented a differentiated learning approach based on Tomlinson's Theory, which focuses on adjusting content, process, product, and learning environment according to the individual needs of students. This school has students with various special needs, including hearing impairments, speech impairments, ADHD, slow learners, and special emotional needs, who require innovative learning strategies in order to actively participate in Arabic language learning. This study aims to investigate innovations in Arabic language learning based on curriculum differentiation according to Tomlinson's Theory at MTs Wachid Hasyim Surabaya. A qualitative approach using a single case study method was used to identify the forms of learning innovation applied and their effectiveness in improving Arabic language comprehension and skills for students with special needs. Data collection was conducted through classroom observation, interviews with teachers and students, and analysis of learning documents. The results showed that the application of Tomlinson's Theory in differentiated learning had a positive impact on the motivation, participation, and understanding of students with special needs in Arabic language learning. The learning innovations applied included: (1) content differentiation through adjusting the level of complexity of vocabulary and sentence structure; (2) process differentiation through the use of multisensory methods and visual-auditory-based interactive media; (3) product differentiation through varying assessment forms and tasks according to student abilities; and (4) learning environment differentiation through flexible and supportive classroom settings. These strategies have been proven to help increase student engagement in learning. Thus, this Tomlinson Theory-based learning differentiation model can be used as a reference in the development of Arabic language learning in other inclusive schools.